What Has Man Made of Man? An Examination of the Epic Self - Saputra, Buyung Ade; Sari, Hanifah Yulia; Indriyani, Vivi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This research examines the concept of the Epic Self in William Wordsworth's poem